Crown Shaped Edge Multiband Antenna Design for 5G and X-Band Applications - Hakanoglu, Baris Gurcan; Kilic, Veli Tayfun; Altindis, Fatih; Turkmen, Mustafa (Springer, 2023)
Nowadays we are experiencing the fifth-generation (5G) technology with new frequency bands to achieve high broadband speed, minimum latency and more developed end user devices. Due to the different frequency ranges for different applications at 5G bands the antennas should support multiband operation in a compact structure. This paper proposes a new multiband microstrip patch antenna design operating at mid band 5G frequencies and in the X band. The structure of the antenna includes simply loading the top radiating edge with rhombic shaped stubs and slots. This configuration yields the antenna to have resonances at multiple frequencies based on the fact that the stubs and slots affect capacitive and inductive impedances on the lower and higher operating frequencies of the antenna. The unique design enables the antenna to have reasonably high gains at four different bands of 6.76 dBi, 6.47 dBi, 7.76 dBi and 5.51 dBi at 3.34 GHz, 4.61 GHz, 6.01 and 8.02 GHz, respectively. Also, the simulated antenna has been manufactured and measured. The measurement results are in good agreement with the simulation results. The proposed design can be used with many other frequency bands and dielectric materials as well to achieve multiband operation.
Kilic, Veli Tayfun/0000-0001-6806-9053; Hakanoglu, Baris Gurcan/0000-0002-5157-8414
Keywords: Microstrip Patch Antennas; Multiband Operation; 5G Mobile Communication; Wireless Networks